Music performance anxiety: the role of early parenting experiences and cognitive schemas - Kirsner, Jennifer; Wilson, Sarah J.; Osborne, Margaret S. (Frontiers in Psychology, 2023)
The aim of this research was to explore the impact of childhood experiences with parents along with patterns of dysfunctional cognitive schemas that develop through childhood (‘Early Maladaptive Schemas’; EMSs) on the manifestation and severity of music performance anxiety (MPA) in adulthood. Study 1 employed 100 adult professional, amateur, and tertiary student classical musicians from across Australia. Participants completed the Young Schema Questionnaire (Young, 2005) and the Kenny Music Performance Anxiety Inventory (Kenny, 2011). Study 2 included eight participants from Study 1, five of whom scored 1.5 standard deviations or more above the mean K-MPAI score and three of whom scored 1.5 standard deviations or more below the mean K-MPAI score. Participants were interviewed about experiences of parenting during childhood and adolescence, along with their experiences of MPA and musical training. Interpretative phenomenological analysis was used to explore themes in the interview data. Study 1 factor analysis revealed four higher-order EMS factors, F(4, 95) = 13.74, p < .001, one of which was a significant predictor of MPA, t(99) = 3.06, p = .003. This factor comprised themes of failure, catastrophising, and incompetence/dependence. Study 2 qualitative analysis revealed various key parenting themes experienced in childhood that differentiated low- and high-MPA scorers in adulthood. Findings from both studies are discussed in light of clinical applications and interventions, and implications for both parents and music educators.